2020
DOI: 10.1039/c9ra06864c
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptides fromBombyx mori: a splendid immune defense response in silkworms

Abstract: AMPs produced by B. mori induced by microbial challenge in the fat body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 92 publications
(171 reference statements)
0
27
0
Order By: Relevance
“…Insects oils are rich in other putative antimicrobials such as antimicrobial peptides (AMP), polymers, and chemical complexes that could act alone or synergically with fatty acids [ 34 , 35 , 52 , 53 ]. A recent “in silico” transcriptomic analysis of H. illucens brought to the identification of 57 peptides with putative antimicrobial activity and belonging to cecropin and defensin families [ 54 ]; on the other hand, six families of AMP have been identified in B. mori , namely cecropin, defensin, moricin, gloverin, attacin, and lebocin [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insects oils are rich in other putative antimicrobials such as antimicrobial peptides (AMP), polymers, and chemical complexes that could act alone or synergically with fatty acids [ 34 , 35 , 52 , 53 ]. A recent “in silico” transcriptomic analysis of H. illucens brought to the identification of 57 peptides with putative antimicrobial activity and belonging to cecropin and defensin families [ 54 ]; on the other hand, six families of AMP have been identified in B. mori , namely cecropin, defensin, moricin, gloverin, attacin, and lebocin [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMP study is based on the discovery of the antimicrobial activity of peptides in fluids and tissues of humans and mammals [ 31 ]. Subsequent studies showed that AMPs play an important role in the immune system of all living beings [ 32 ]. The development of physicochemical methods for studying molecular processes made it possible to describe the structural features of peptides and to reveal some connections between the properties of AMPs.…”
Section: Brief History Of Research Physicochemical Properties CLmentioning
confidence: 99%
“…Former studies about AMP antimicrobial activity against B. thuringiensis showed that AMP encoding genes from Trichoplusia ni were increased in insects which were previously exposed to these bacteria [ 63 ]. Also, cecropins, moricins and gloverins from Bombyx mori showed a high antimicrobial activity against B. thuringiensis [ 64 ]. In Spodoptera spp, the response to B. thuringiensis infection depends on several biological factors, such as the production of AMPs [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…When this barrier is broken, invading microorganisms are exposed to a variety of cellular and humoral processes that support the host defense [ 4 ]. In that regard, the production of antimicrobial peptides (AMPs) is one of the key responses in the humoral immune system [ 5 ].…”
Section: Introductionmentioning
confidence: 99%